Analysis of Socio-Economic Determinants of Child Labour In North Eastern Nigeria - Ibrahim Musa; Sule Magaji; Ahmad Mohammad Tsauni (Inclusive Society and Sustainability Studies, 2022)
This study examines major socio-economic determinants of child labour in North-Eastern Nigeria. The study employs multistage sampling techniques to obtain required data from selected local government areas in three states of North Eastern Nigeria, namely, Adamawa, Bauchi, and Yobe States. Structured questionnaires were administered to 810 children and their household heads in three wards of each local government area selected. The data obtained was analyzed using the Tobit Model. The result shows that socio-economic determinants of child labour comprise children’s age, children’s gender, children’s relationship with household head, household head’s education, household head’s occupation, and poverty, which is measured by household head’s income, family size, access to clean piped water, and distance from school. Among them, some were found to be statistically significant at varying levels. Therefore, the study recommends necessary actions such as enlightenment on the effects of child labour, severe punishment of those found involved in child labour related activities, and the need for the government to make adequate provision for basic infrastructure.